I feel machine - Able, Krent; Hanshaw, Julian, 1971-; Svetoft, Erik; Brown, Box; Tan, Shaun; Walden, Tillie, 1996- (SelfMadeHero, 2018)
In I Feel machine, six award-winning comic book artists explore the strange interplay between humanity and technology. These visionary short fictions, by turns cautionary and celebratory, offer an electrifying glimpse into our collective future.